Transgenic tobacco plants with reduced capability to detoxify reactive oxygen intermediates are hyperresponsive to pathogen infection - Mittler, Ron (National Academy of Sciences, 1999)
Reactive oxygen intermediates (ROI) play a critical role in the defense of plants against invading pathogens. Produced during the “oxidative burst,” they are thought to activate programmed cell death (PCD) and induce antimicrobial defenses such as pathogenesis-related proteins. It was shown recently that during the interaction of plants with pathogens, the expression of ROI-detoxifying enzymes such as ascorbate peroxidase (APX) and catalase (CAT) is suppressed. It was suggested that this suppression, occurring upon pathogen recognition and coinciding with an enhanced rate of ROI production, plays a key role in elevating cellular ROI levels, thereby potentiating the induction of PCD and other defenses. To examine the relationship between the suppression of antioxidative mechanisms and the induction of PCD and other defenses during pathogen attack, we studied the interaction between transgenic antisense tobacco plants with reduced APX or CAT and a bacterial pathogen that triggers the hypersensitive response. Transgenic plants with reduced capability to detoxify ROI (i.e., antisense APX or CAT) were found to be hyperresponsive to pathogen attack. They activated PCD in response to low amounts of pathogens that did not trigger the activation of PCD in control plants. Our findings support the hypothesis that suppression of ROI-scavenging enzymes during the hypersensitive response plays an important role in enhancing pathogen-induced PCD.